Numerical Simulation of the Static and Dynamic Aerodynamics of a UAV under Wake Flows - Bai-gang Mi; Hao Zhan (Journal of Advanced Transportation)
Frequent flight conflicts will be observed as the number of aircrafts increases, and such conflicts will cause unprecedented challenges in flight safety; thus, the flight characteristics of small aircrafts under the wake flow of a large airliner should be thoroughly analyzed. Combined with the sliding mesh technique, a computational fluid dynamics (CFD) method is proposed in this paper to simulate three wake flow patterns, i.e., wingtip vortex, jet flow, and propeller slipstream, and then, the static and dynamic derivatives that represent the stability of the fly wing under the wake flow are identified by using the least squares method. The results demonstrate that both the steady and unsteady aerodynamics of the fly wing are affected by wake flows: wingtip vortices increase the lift-to-drag ratio and considerably change the dynamic damping; jet flow reduces both the static and dynamic damping; and propeller slipstream leads to slow variations in the dynamic damping and decreases in the lift-to-drag ratio.